Lifespan Navigation-Building Framework for Children/Youth With Neurodisability and Their Families. Issue 3 (July 2022) - Hébert, Michèle L.; Nicholas, David B.; Lach, Lucyna M.; Mitchell, Wendy; Zwicker, Jennifer; Bradley, Wenda; Litman, Sandy; Gardiner, Emily; Miller, Anton R.
This study served to conceptualize neurodisability (ND) navigation-building. Capacity-building toward wide-reaching ND navigation or help-seeking service lacks empirical evidence. Researchers widely agree that a system-wide framework is absent. While research emphasizes service-level findings, other jurisdiction- and policy-level insights are lacking. Using Collective Community Impact and Participatory Action Research, government and nongovernment organizations in three Canadian regions implemented novel cross-jurisdictional initiatives to improve navigation capacity. Family-partners and other stakeholders systematically engaged in discussions. Grounded in qualitative thematic design, we sought to unveil connections between emerging themes. These themes led to stakeholders co-constructing an intersectoral navigation-building conceptualization. A framework was essential for highlighting change-levers and potential replication in other jurisdictions/landscapes. Finally, practice and policy implications compatible with an ecosystem model are presented.